Chitosan antimicrobial and eliciting properties for pest control in agriculture: a review - Xing, Ke; Zhu, Xiao; Peng, Xue; Qin, Sheng (Agronomy for sustainable development, 2015)
In agriculture, current control of pathogens relies mainly on chemical fertilizers and pesticides. However, alternative solutions are needed due to concerns for public health, environmental protection, and development of resistant pests. Chitosan is a nontoxic, biodegradable biopolymer showing antimicrobial and plant-immunity eliciting properties. Here, we review chitosan antimicrobial activities, modes of action, and the elicitation of plant defense responses. The major points are the following: (1) Chitosan exhibits various inhibitory efficiency against bacteria, fungi, and viruses; (2) the five main modes of action of chitosan are electrostatic interactions, plasma membrane damage mechanism, chitosan-DNA/RNA interactions, metal chelation capacity of chitosan, and deposition onto the microbial surface; (3) the elicitation of plant defense responses by chitosan may be related to various pathogenesis-related proteins, defense-related enzymes, and secondary metabolites accumulation, as well as the complex signal transduction network. The facing problems and strategies for antimicrobial mechanism research and agricultural application of chitosan are also discussed.